Development of a safe drug administration assessment instrument for nursing students - Karen Domínguez Cancino; Marisol Arias; Erika Caballero; Eliana Escudero
Objective: to determine the content and face validity of a safe drug administration assessment instrument for nursing students. Method: quantitative, descriptive study. The literature on medication errors made by students was analyzed, and an instrument was developed using the Architecture of Integrated Information Systems and the Work Breakdown Structure. Face validity was analyzed using the nominal technique, with experts in education, management, research and/or clinical practice. Results: nine experts participated in the validation process, which resulted in an instrument containing 8 sub-processes and 58 items, adjusted to the simulation environment and to clinical practice. Conclusion: the instrument may be used for the evaluation of safe drug administration by nursing students, especially in a simulation environment.